Dual-band Doherty power amplifier with the improvement of reactance compensation technique for LTE frequency operations / Yu Li Ming - Yu , Li Ming (2021)
A dual-band selection of Doherty power amplifier employing a Reactance Compensation Technique (RCT) with Gallium Nitride High-Electron-Mobility-Transistor (GaN HEMT) technology is presented. In this dissertation, the focus has been given to the design power amplifier in Doherty configuration, where it can operate at dual-band frequency and enhanced performances at 6 dB back-off from saturation power. This project applied lossy matching circuit for the input matching network and incorporated the primary motivation of using RCT and third harmonic tuning for the output matching network. The DPA designed can achieve satisfying results for the frequency of 0.8 and 2.1 GHz. The implementation is suitable for two-way radio application, particularly for LTE frequency operation. The results of the proposed concept are validated through simulation by using Advanced Design System (ADS). The measured results of the prototype board report accepted performance over the desired frequency. (ie. the maximum power level of 40.5 dBm, 6 dB back-off efficiency of 43% and 47% and gain of 10 dB approximately at 0.8 GHz and 2.1 GHz, respectively).